Beta2-adrenergic signaling affects the phenotype of human cardiac progenitor cells through EMT modulation. (January 2018) - Pagano, Francesca; Angelini, Francesco; Siciliano, Camilla; Tasciotti, Julia; Mangino, Giorgio; De Falco, Elena; Carnevale, Roberto; Sciarretta, Sebastiano; Frati, Giacomo; Chimenti, Isotta
Graphical abstract: Abstract: Human cardiac progenitor cells (CPCs) offer great promises to cardiac cell therapy for heart failure. Many in vivo studies have shown their therapeutic benefits, paving the way for clinical translation. The 3D model of cardiospheres (CSs) represents a unique niche-like in vitro microenvironment, which includes CPCs and supporting cells. CSs have been shown to form through a process mediated by epithelial-to-mesenchymal transition (EMT). β2-Adrenergic signaling significantly affects stem/progenitor cells activation and mobilization in multiple tissues, and crosstalk between β2-adrenergic signaling and EMT processes has been reported. In the present study, we aimed at investigating the biological response of CSs to β2-adrenergic stimuli, focusing on EMT modulation in the 3D culture system of CSs. We treated human CSs and CS-derived cells (CDCs) with the β2-blocker butoxamine (BUT), using either untreated or β2 agonist (clenbuterol) treated CDCs as control. BUT-treated CS-forming cells displayed increased migration capacity and a significant increase in their CS-forming ability, consistently associated with increased expression of EMT-related genes, such as Snai1. Moreover, long-term BUT-treated CDCs contained a lower percentage of CD90+ cells, and this feature has been previously correlated with higher cardiogenic and therapeutic potential of the CDCs population. In addition, long-term BUT-treated CDCs had an increased ratio of collagen-III/collagen-I gene expression levels, and showed decreased release of inflammatory cytokines, overall supporting a less fibrosis-prone phenotype. In conclusion, β2 adrenergic receptor block positively affected the stemness vs commitment balance within CSs through the modulation of type1-EMT (so called "developmental"). These results further highlight type-1 EMT to be a key process affecting the features of resident cardiac progenitor cells, and mediating their response to the microenvironment.